Microwave synthesis method for dandelion-like copper cobaltite nanoparticles and its usage for the preconcentration of cadmium at trace levels in tap water and Za'atar tea samples - Agbulak, Asli; Bodur, Sezin Erarpat; Bakirdere, Sezgin (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2025)
In this work, a sensitive and rapid analytical method for the determination of cadmium at trace levels in tap water and za'atar tea samples was established. Dispersive solid phase extraction (d-SPE) method was used for the preconcentration of analyte. Copper cobaltite (CuCo2O4) sorbent was firstly produced by microwave-assisted method and characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR) and scanning electron microscope (SEM). Under the optimum d-SPE-FAAS conditions, limit of detection (LOD), limit of quantitation (LOQ), linear dynamic range (LDR) were calculated as 0.64, 2.12 and 2.5-77.3 mu g/kg, respectively. Recovery experiments were done for tap water and za'atar tea samples. Percent recovery results for the spiked samples ranged from 95.1 % to 123.3 %. This is the first study where CuCo2O4 was used as sorbent in dSPE method for the preconcentration of cadmium at trace levels and microwave-assisted synthesis method was used to generate CuCo2O4 sorbent. In addition, cadmium at trace levels in Za'atar tea samples is firstly determined by the developed d-SPE-FAAS method in this study.
Keywords: Cadmium; Flame atomic absorption spectrometry; Copper cobaltite; Dispersive solid phase extraction; Za'atar tea; Tap water; SOLID-PHASE EXTRACTION; FE3O4 NANOPARTICLES; ELECTRODE; PERFORMANCE; Chemistry; Food Science & Technology